2023
DOI: 10.3389/fgene.2023.1075767
|View full text |Cite
|
Sign up to set email alerts
|

Combining high carotenoid, grain protein content and rust resistance in wheat for food and nutritional security

Abstract: Globally, malnutrition has given birth to an alarming predicament, especially in developing countries, and has extensively shifted consumer preferences from conventional high-energy diets to a nutritionally balanced, cost-effective, sustainable, and healthy lifestyle. In keeping with this view and the mandate for developing high-yielding, disease-resistant biofortified staple food (wheat) for catering to the demand-driven market, the current research aimed at stacking together the enhanced grain protein conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…In more recent study, genes were pyramided for high GPC, high grain carotenoid content and resistance to all the three rusts in elite wheat cv. HD2967 (Padhy et al 2023) and two Fhb loci were pyramided in high-quality soft wheat cultivar Yangmai 15 (Hu et al 2023). A wide array of resistance genes (> 220)…”
Section: Evaluation Of Ve Best Mas-derived Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…In more recent study, genes were pyramided for high GPC, high grain carotenoid content and resistance to all the three rusts in elite wheat cv. HD2967 (Padhy et al 2023) and two Fhb loci were pyramided in high-quality soft wheat cultivar Yangmai 15 (Hu et al 2023). A wide array of resistance genes (> 220)…”
Section: Evaluation Of Ve Best Mas-derived Linesmentioning
confidence: 99%
“…Another attribute of the gene Gpc-B1 is its association with Yr36, which is, an e cient high-temperature adult-plant (HTAP) stripe-rust resistance gene (Uauy et al 2005). Therefore, the use of Gpc-B1 is particularly useful for improvement of both grain nutritional quality and disease resistance in wheat (Padhy et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Boba based their analysis of fusarium susceptibility on transgenic flax that produces excessive carotenoid and found that transgenic flax showed greater resistance to pathogen infection [31]. In order to increase the protein content, carotenoid content and disease resistance of wheat, we overexpressed the y and GPCB1 genes to increase the carotenoid content and protein content of wheat overexpression of these two genes also increased wheat resistance to leaf rust linkage reaction [32]. Alleles of the DN1 and DN2 genes with resistance to wheat aphids by Heng-Moss were affected by carotenoid concentrations [33].…”
Section: Disease Resistance and Secondary Metabolitesmentioning
confidence: 99%
“…Once the properties of the family of compounds and their concentration in essential oils are known, their effects (beneficial or harmful) can be determined. The biological properties of EU are determined by their main components [16]. The widespread application of EU in aromatherapy reveals their effect on the immune system of the human body.…”
Section: Globalize Your Researchmentioning
confidence: 99%